Renovation of JGC-30 Coal Feeding Belt in Thermal Power Plant - Yang, Liu; Abidin, Muhammad As’ad (Syntax Literate, 2024)
The coal feeder of our company's pulverizing system adopts JGC-30 weighing metering coal feeder. The raw coal in the raw coal hopper falls onto the coal feeder belt through the coal drop port by its own gravity. The existing design of high belt skirt on both sides is 40mm. A small amount of coal blocks falls off on both sides of the belt during the falling process. Due to the wind force of the coal feeder sealing wind and the operation of the belt, a small amount of coal blocks are scattered and stuck at the coal feeder weighing device. The inaccurate coal quantity measurement leads to large fluctuations in the coal feeding quantity of the pulverizing system, that will makes inducing abnormal vibration of the coal mill, insufficient coal powder output, large amount of slag discharge from the coal mill and other problems, which seriously affect the safe and stable operation of the pulverizing system. In this regard, the coal feeding belt was modified, and the skirts on both sides of the coal feeder were increased to 60mm. After the modification, it can be ensured that the raw coal does not fall from the skirts on both sides during the operation of the coal feeder, thereby solving the problem of inaccurate coal quantity measurement caused by coal blocks stuck in the weighing device. This study aims to address the problem by modifying the coal feeder belt, namely by increasing the skirt height on both sides of the belt from 40mm to 60mm. The method applied was to adjust the belt skirt design directly on the operating coal feeder, followed by operational testing to evaluate the effectiveness of the modification in preventing coal falling from the belt side. Results show that after increasing the height of the skirt belt, there is no more coal falling during coal feeder operation. Coal measurement became more accurate, which had a positive impact on coal feeding stability, reduced vibration in the coal mill, as well as increased fine coal output and reduced the amount of slag produced.